Ex vivo comparison of ultrasonographic intestinal wall layering with histology in horses: A feasibilty study. Issue 3 (27th December 2020) - Bevevino, Kari E.; Edwards, John F.; Cohen, Noah D.; de Solis, Cristobal Navas
Abstract: Ultrasonography is increasingly being used as a clinical and research method for evaluating the gastrointestinal tract in horses, however published studies comparing ultrasonographic and histologic characteristics of equine intestinal wall layers are currently lacking. Objectives of this prospective, observational, methods comparison, case series study were to compare the layering pattern and thickness of the intestinal wall layers determined using ex vivo and in vivo ultrasonography with those determined using histology. For the ex vivo study, twelve horses were euthanized for reasons unrelated to gastrointestinal disease, and samples of the duodenum, jejunum, ileum, cecum, right dorsal colon, and small colon were collected and imaged sonographically ex vivo in an isotonic bath within 1 hour of euthanasia. For the in vivo study, ultrasonography was performed in four clinical cases, and findings were compared with histopathology. A 5‐layer pattern of alternating echogenicity was observed in 70 of 72 ex vivo samples. Agreement between histologic and sonographic measurements was deemed good for all segments except the ileum. Formalin fixation did not alter the sonographic appearance or wall measurements. Findings from the four clinical cases illustrated the feasibility of also obtaining ultrasonographic images with sufficient sonographic detail in vivo to recognize wall layering and obtain comparable results to pathologic lesions. Findings from the current study can serve as background for future studies comparing ultrasonographic characteristics of the intestinal wall in horses with different gastrointestinal diseases.